(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2025)
Continuous Professional Development (CPD) is critical to enhancing the pedagogical competence and professional growth of English language lecturers in teacher education institutions. However, in Nigeria, lecturers in Colleges of Education face persistent challenges in accessing structured CPD opportunities, including inadequate institutional support, limited funding, and overreliance on donor-driven initiatives. This paper presents a conceptual analysis of the professional development needs of English lecturers in two Colleges of Education in Jigawa State, situating the discussion within global best practices for teacher education. Drawing on recent literature and international competency frameworks, the paper highlights five essential CPD domains: pedagogical knowledge, language proficiency, assessment literacy, digital teaching competence, and professional values. It argues for the adoption of sustainable, institutionally driven CPD models—such as mentorship, reflective practice, peer observation, and blended learning approaches—that align with both local needs and international standards. The paper contributes a theoretical framework for strengthening CPD in Nigerian Colleges of Education, providing evidence-based recommendations for policymakers, institutional leaders, and development partners. Ultimately, it underscores the urgent need to institutionalize CPD as a strategic component of teacher education reforms to improve the quality of English language instruction and better prepare future teachers for 21st-century classrooms.